Personalized warm-up strategies for adult athletes: a meta-analysis based on athletic level, gender, and region - Xu, Y.; Dai, J.; Liang, X.; Zhang, Y. (Frontiers in Physiology, 2025)
Objective: This study aimed to investigate the acute effects of high-intensity parallel squats (HIPS) on lower-limb explosive power in adult athletes, with a specific focus on how athletic calibre, sex and geographic origin modulate the ensuing potentiation response (PAP/PAPE)—the transient increase in muscular power or performance that follows heavy resistance exercise., and provide evidence for designing precision Warm-up protocols.